Determinant Variables, Enteric Pathogen Burden, Gut Function and Immune-related Inflammatory Biomarkers Associated With Childhood Malnutrition: A Prospective Case–Control Study in Northeastern Brazil. Issue 12 (December 2017) - Lima, Aldo A. M.; Leite, Álvaro M.; Di Moura, Alessandra; Lima, Noélia L.; Soares, Alberto M.; Abreu, Cláudia B.; Filho, José Quirino; Mota, Rosa M. S.; Lima, Ila F. N.; Havt, Alexandre; Medeiros, Pedro H. Q. S.; Prata, Mara M. G.; et al.
Abstract : Malnutrition results in serious consequences for growth and cognitive development in children. We studied select child and maternal biologic factors, socioeconomic factors, enteric pathogenic burden and gut function biomarkers in 402 children 6–24 months of age in Northeastern Brazil. In this prospective case–control study, not being fed colostrum [odds ratio (OR): 3.29, 95% confidence interval (CI): 1.73–6.26], maternal age ≥18 years (OR: 1.88, 95% CI: 1.10–3.22) and no electric fan (OR: 2.46, 95% CI: 1.22–4.96) or bicycle (OR: 1.80, 95% CI: 1.10–2.95) in the household were positively associated, and higher birth weight (OR: 0.27, 95% CI: 0.19–0.38), larger head circumference (OR: 0.74, 95% CI: 0.66–0.82) and shortness of breath in the last 2 weeks (OR: 0.49, 95% CI: 0.27–0.90) were negatively associated with malnutrition. Subclinical enteric pathogen infections were common, and enteroaggregative Escherichia coli infections were more prevalent in malnourished children ( P = 0.045). Biomarkers such as the lactulose–mannitol test, myeloperoxidase, neopterin and calprotectin were highly elevated in both malnourished and nourished children. Nourished children had a better systemic immune response than the malnourished children, as detected by elevated serum amyloid A-1 and soluble cluster of differentiation protein 14 biomarkers ( P < 0.001). Serum amyloid A-1 and soluble cluster of differentiation protein 14 were also associated with better nutritional Z scores. Neonatal, maternal and socioeconomic factors were associated with malnutrition in children. There was a substantial subclinical enteric pathogen burden, particularly with enteroaggregative E. coli, in malnourished children. Abstract : Supplemental Digital Content is available in the text.